Atlas of the Ethiopian rural economy - Tadesse, Mulugeta; Alemu, Betre; Bekele, Gashaw; Chamberlin, Jordan; Benson, Todd; Tebekew, Tewodros (International Food Policy Research Institute, 2006)
"One important impediment to improved policies and investments for poor and rural people in Africa has been a lack of data on actual conditions. To begin to help fill this data gap, the International Food Policy Research Institute (IFPRI) worked closely with Ethiopia’s Central Statistical Agency to produce the Atlas of the Ethiopian Rural Economy. This Atlas gives a comprehensive view of rural Ethiopia in the areas of production, infrastructure, markets, natural resources, agroclimate, social indicators, institutions, and demographics. By giving a full and multilayered picture of conditions in rural Ethiopia, these maps should facilitate the design of interventions that can contribute to a path of sustained growth for the Ethiopian economy. They should also help policymakers and development practitioners target interventions to the people and communities who need them most." -- from Foreword by Joachim von Braun